Analisis Kebijakan Pendidikan Era Khullafah Rasyidin - Rido Putra; Nafsan; Nurkha Mariya (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2023)
This study describes Islamic education policies in the Khullafah Rasyidin era and their impact on the development of Islamic education. This study aimed to describe how Islamic education policies were in the Khullafah Rasyidin era, which had a major impact on the development of Islamic education at that time. This study was library research with a qualitative approach. Sources of data were obtained through in-depth studies of various literatures such as books, articles, journals, and other supporting sources. The results showed that the era of the Khullafah Rasyidin leadership was divided into four periods, namely the Khalifah Abu Bakar As-Siddiq, Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib for 32 years. The most rapid progress of Islamic education occurred during the era of Khalifah Umar bin Khattab through several important policies, namely: First: the issuance of an order by the Khalifah Umar bin Khattab to the Islamic commanders containing orders to build mosques as a means of education and worship in every successful area controlled by Muslims. Second, Khalifah Umar bin Khattab appointed several scholars to teach in various areas of Islamic rule. Third, he ensured the welfare of educational personnel. Fourth, he gave rewards to theologian who produced a work in the form of a book in gold equivalent to the weight of the work.